Optimum generation mix for Malaysia's additional capacity using evolutionary programming - Abdul Mutalib, N. A. Husna; Dahlan, N. Y.; Abon, S. A.; Rajemi, Mohamad Farizal; Mohd Nawi, Mohd Nasrun; Baharum, Faizal (2014)
Energy Commission Malaysia is targeting 4100 MW of power generation capacity via competitive bidding to replace capacity from the 1st generation Power Purchase Agreement (PPA) that will be retired from 2015 to 2017 and to cater for future demand growth. Malaysia's generation mix has been long time dependence on a single fuel.This over-dependency is not a good option for long-term energy sustainability and security. This has led Malaysia to find other alternative resources to generate electricity.Some possible options are: 1) coal, 2) nuclear and 3) renewable energy (RE). This paper proposes to determine optimum alternative resources of generation mix for Malaysia's additional capacity in 2015 using Evolutionary Programming (EP) at the least cost. The model takes into account characteristics associated with different technologies, such as the investment cost, the O&M cost, the fuel cost and the heat rate. This paper considers four new expansion candidates i.e. coal, natural gas, nuclear and renewable energy as the major power generation sources. Result shows that, the optimum generation mix for Malaysia's additional capacity in 2015 will be 67.9% is from coal, 22.51% from natural gas, 8.21% from nuclear and 1.25% from RE.